Pathology in elephant dentition—two addenda - Parker, Ian SC (Pachyderm, 2021)
Parker (2017)* described a pathological condition of molar/alveola abscesses in elephants (Loxodonta africana). Instances cited were 84 in Uganda—all in Murchison Falls National Park (NP)—four single cases from different elephant groups in Kenya and one from Zimbabwe. This note extends those observations to a further six cases from central Mkomasi 1 National Park (then Game Reserve), Tanzania, that were overlooked at the time. The material was obtained during animals culled in 1969 and as described in Parker (2017). They are presented in Table 1. Keywords Abscesses, molars, lower jaw. Mots clés Abcès, molaires, mâchoire inférieure.